Polyaniline–MnO2 coaxial nanofiber with hierarchical structure for high-performance supercapacitors - Jiang, Hao (2013)
We demonstrated the facile loading of ultrafine and loosened K-birnessite MnO2 floccules on the surface of polyaniline (PANI) nanofibers by simply soaking the polyaniline nanofibers in a KMnO4 aqueous solution for electrochemical energy storage applications. The as-prepared PANI–MnO2 coaxial nanofibers with optimal composition, when applied as an electrode, exhibited a high specific capacitance (383 F g−1 at 0.5 A g−1) with good rate and cycling stability in 1 M Na2SO4 aqueous solution. Such intriguing electrochemical performance is mainly attributed to the synergistic effects of the combined pseudo-capacitive contributions from the core and shell. The present findings promoted the development of advanced electrode materials, exhibiting huge potential for supercapacitors.